Terrorism and international business: A research agenda - Czinkota, Michael R; Knight, Gary; Liesch, Peter W; Steen, John (Journal of International Business Studies, 2010)
Terrorism threatens international business (IB) through its direct and indirect effects. As governments tighten security at public sites, businesses have become more attractive terrorist targets, with important implications for the operations and performance of multinational firms. While terrorism has been substantially studied in other fields, there has been little scholarly research to address terrorism and the distinctive challenges that it poses for IB. In this article we conceptualize terrorism in relation to IB. We provide background on the dimensions and effects of terrorism, and develop a theoretical grounding for terrorism research by drawing on the literature from IB, economics, political science, and other fields. After discussing findings from the literature review, we offer a comprehensive agenda for future research regarding the relationship between terrorism and IB. Our agenda emphasizes the effects of terrorism, organizational preparedness, company strategy and performance, global supply chain and distribution channels, and human resource issues. Our review helps establish a baseline for future empirical research. Consistent with the early stages of research, IB scholars are encouraged to offer useful perspectives and effective solutions that shed needed light on terrorism and help reduce its destructive effects for IB and multinational firms.